Genetic variants of interleukin-4 gene in autoimmune thyroid diseases: An updated meta-analysis. (March 2015) - Shen, Xiaokun; Yan, Xingqiang; Xie, Bojian; Xu, Dong; Wang, Kuifeng; Zhu, Jiansheng; Li, Jichen; Zhang, Xiaohua; Cao, Feilin
Abstract Autoimmune thyroid diseases (AITDs) including Graves' disease (GD) and Hashimoto's thyroiditis (HT) are common autoimmune endocrine disorders. Interleukin-4 (IL-4), a cytokine secreted by T cells, plays a critical role in antigen-specific Th2 responses. The IL-4 gene is highly polymorphic and it has been reported that the polymorphism at –590 (T/C, rs2243250) in the promoter region of IL-4 may contribute to the development of AITDs. Recently, several case-control studies have examined the association of genetic variants of IL-4 with AITDs. However, the results of these studies remain conflicting. To systematically study the role of IL-4 in the pathogenesis of AITDs, we conducted a meta-analysis including 11 eligible studies (1847 cases and 2068 healthy controls). Fixed-effect or random-effect models were used to calculate pooled odds ratios (ORs) with corresponding 95% confidence intervals (CIs). Our results revealed a significant association between the IL-4 genetic variant (−590, T/C, rs2243250) and the risk of developing AITDs (TC + TT versus TT genotype: OR = 1.83, 95% CI = 1.083–3.091, p = 0.024). These findings demonstrate that the IL-4 rs2243250 genetic variant might play a key role in the development of AITDs.